PSYCHOLOGICAL INTERVENTIONS AS A TOOL FOR INCREASING THE EFFECTIVENESS OF DISEASE TREATMENT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article examines the impact of psychological interventions on treatment outcomes for diseases of various etiologies. It examines the use of cognitive behavioral therapy, meditation, hypnosis, and other methods to improve clinical outcomes and enhance patients' quality of life. It also examines the mechanisms by which psychological factors influence physical health and prospects for further research in this area.